Нелінійні моди коливань і складна поведінка маятникової системи у магнітному полі - Сурганова, Юлія Едуардівна; Міхлін, Юрій Володимирович (Інститут прикладних проблем механіки і математики імені Я. С. Підстригача НАН України, 2023)
The paper is dedicated to investigations of local and coupled vibration modes of the damped system consisting of two connected pendulums having significantly different masses under the action of a magnetic force and a damper. Such modes are constructed using the multiple scales method; the stability of the modes is also analysed. Analytical results are compared with numerical simulation when the Runge-Kutta method and the spectrum presentation are used. An appearance of the complex behaviour when the system parameters change is found and investigated.
Nonlinear vibration modes and complex behavior of a pendulum system under a magnetic field
Keywords: нелінійні моди коливань; маятники; маятникова система; магнітне поле; електромагнітна сила; демпфування